The Total Brain Workout: Vol. 1 : To Sharpen Your Mind, Improve Your Memory & Keep Your Brain Fit - Marcel Danesi (Harlequin India Pvt. Ltd, 2015)
Boost your brain power! did you know that different parts of your brain control different functions and that with exercise, you can make each part of your brain stronger? in the total brain workout you'll find fun, challenging and absorbing puzzles designed to specifically target the core parts of your brain that control language, logic, memory, reasoning and visual perception. Each set of puzzles ranges from easy to challenging and is presented with information on the area of your brain being targeted and the functions it controls, so you can customize your own workout to the specific areas you want to improve. Flex your mental muscle with: word searches cryptograms optical illusions logic puzzle skin ship puzzles visualization puzzles and much more! marcel danesi is a professor of anthropology at the university of toronto. He has published extensively on puzzles and is the author of the puzzle instinct, increase your puzzle iq and sudoku: 215 puzzles from beginner to expert.